Analysis of flood-prone areas in DKI Jakarta Province using Clustering Method - Aditya, Randy Daffa; Habibi, Muhammad Abdul Aziz (Universitas Pakuan, 2024)
The objective of this research is to ascertain the patterns and organization of flood-affected areas in Jakarta. The dataset of flood incidents in the DKI Jakarta Province in 2020 served as the data source for this study. The research employed three methods: K-Means, K-Medoid, and Hierarchical Clustering. Of these, Hierarchical Clustering produced the best grouping in comparison to the other methods. The findings of the study show that the flood-affected areas in DKI Jakarta are classified into three groups: safe (cluster 1), moderate (cluster 2), and vulnerable (cluster 3). The districts of Cengkareng, Jatinegara, and Pulogadung are among the vulnerable areas. ABSTRAK Tujuan penelitian ini adalah untuk mengetahui pola dan penataan wilayah terdampak banjir di Jakarta. Dataset kejadian banjir di Provinsi DKI Jakarta tahun 2020 dijadikan sebagai sumber data penelitian ini. Penelitian ini menggunakan tiga metode: K-Means, K-Medoid, dan Hierarchical Clustering. Dari ketiga metode tersebut, Hierarchical Clustering menghasilkan pengelompokan terbaik dibandingkan dengan metode lainnya. Temuan penelitian menunjukkan bahwa wilayah terdampak banjir di DKI Jakarta diklasifikasikan menjadi tiga kelompok: aman (kluster 1), sedang (kluster 2), dan rentan (kluster 3). Kecamatan Cengkareng, Jatinegara, dan Pulogadung termasuk wilayah yang rentan.